Time-varying channel estimation for LTE uplink SC-FDMA system with multi-user - Li-hua YANG; Long-xiang YANG; Hong-bo ZHU (Tongxin xuebao)
A novel transform-domain based time-varying channel estimation method is proposed for the long term evolu-tion (LTE) uplink single carrier-frequency division multiple access (SC-FDMA) systems with multi-user.In the transform domain,the channel parameters of the two block pilots were firstly estimated,then the decision-directed (DD) based non-linear interpolation method was employed to estimate the channel parameters of the data symbols.To convenient equalization in the frequency domain,the transform expression of the transform-domain channel and frequency-domain channel was derived,by which the channel estimation in the frequency domain could be directly obtained.Simulation re-sults show that the performance of the proposed method is much better than those of the available methods,and the pro-posed method has a low computational complexity.